A pill full of sunshine. Vitamin D supplementation among polish students - Gaik, Magdalena; Gazda, Dawid; Bogacz, Rafał; Uram, Ewa; Woźniak, Justyna; Womperski, Karol; Magda, Inga; Osuch, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction and purpose of work: Vitamin D has a significant impact on the functioning of the human body. Vitamin D deficiency is a public health problem worldwide in all age groups including Poland. Supplementation is recommended in the general population with the use of cholecalciferol and should be individualized depending on age, body weight, the sun exposure, diet, and lifestyle. The aim of study was to analyze vitamin D supplementation habits among polish students in two divided groups: medical students and non-medical students. Methods: The tool used to carry out the research was a specially constructed, online questionnaire. The survey was completed by 244 students, 126 of whom supplement vitamin D. Pearson’s χ2 test was used to analyze the survey’s results. The processing of the obtained data, statistical calculation and graphs were made using the R program. Results and conclusions: Students of medical faculties are more likely to take vitamin D supplements than students of other faculties. They are significantly more likely to adjust the dose of supplementation to the current guidelines. In 87% of students who tested the level of vitamin D in the blood serum and remember their result, the level of the parameter is ≥30 ng/ml (75 nmol/L), which is below the optimal level for this particular age group. Supplementation improves the quality of life, the benefits of supplementation were noticed by 71.4% of all students. It is necessary to promote the prophylactic habit of vitamin D supplementation.